A nonsense mutation in the COL7A1 gene causes epidermolysis bullosa in Vorderwald cattle. Issue 1 (December 2016) - Pausch, Hubert; Ammermüller, Simon; Wurmser, Christine; Hamann, Henning; Tetens, Jens; Drögemüller, Cord; Fries, Ruedi
Abstract Background The widespread use of individual sires for artificial insemination promotes the propagation of recessive conditions. Inadvertent matings between unnoticed carriers of deleterious alleles may result in the manifestation of fatal phenotypes in their progeny. Breeding consultants and farmers reported on Vorderwald calves with a congenital skin disease. The clinical findings in affected calves were compatible with epidermolysis bullosa. Results Pedigree analysis indicated autosomal recessive inheritance of epidermolysis bullosa in Vorderwald cattle. We genotyped two diseased and 41 healthy animals at 41, 436 single nucleotide polymorphisms and performed whole-genome haplotype-based association testing, which allowed us to map the locus responsible for the skin disease to the distal end of bovine chromosome 22 (P  = 8.0 × 10−14 ). The analysis of whole-genome re-sequencing data of one diseased calf, three obligate mutation carriers and 1682 healthy animals from various bovine breeds revealed a nonsense mutation (rs876174537, p.Arg1588X) in theCOL7A1 gene that segregates with the disease. The same mutation was previously detected in three calves with dystrophic epidermolysis bullosa from the Rotes Höhenvieh cattle breed. We show that diseased animals from Vorderwald and Rotes Höhenvieh cattle are identical by descent for an 8.72 Mb haplotype encompassing rs876174537 indicating they inherited the deleterious allele from a recent common ancestor. Conclusions Autosomal recessive epidermolysis bullosa in Vorderwald and Rotes Höhenvieh cattle is caused by a nonsense mutation in theCOL7A1 gene. Our findings demonstrate that deleterious alleles may segregate across cattle populations without apparent admixture. The identification of the causal mutation now enables the reliable detection of carrier animals. Genome-based mating strategies can avoid inadvertent matings of carrier animals thereby preventing the birth of homozygous calves that suffer from a painful skin disease.